Pendampingan Penguatan Kapasitas Perangkat Desa Seteluk Tengah Dalam Peningkatan Kualitas Pelayanan Publik - Ilham Zitri; Rifaid Rifaid; Darmansyah Darmansyah; Ayatullah Hadi; Azwar Subandi (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
Village Assistance Capacity is the ability to carry out community empowerment activities/actions through village assistance, organization, direction and facilitation. Village Assistance in the implementation of Law Number 6 of 2014 concerning Villages is very important in determining its success. Seeing the current condition of the village which is very heterogeneous in terms of quantity, quality or capacity and even the potential for natural resources and human resources is very varied, the role of village assistance in implementing the Village Law is very important in helping villages carry out the mandate of the Village Law. Seeing the reality of the current condition of the village which is very heterogeneous in terms of quantity, quality or capacity of the Village Government and even the potential for natural resources and human resources is very varied in the context of implementing this Village Law, it is necessary to pay attention to the Village regarding village institutions. With the enactment of Law Number 6 of 2014 concerning Villages, it is hoped that all interests and needs of the village community can be better accommodated. Providing greater opportunities for villages to take care of their own governance. Law Number 6 of 2014 and its implementing regulations have mandated the village government to be more independent in managing the government and various natural resources owned, including the management of village finances.